Jorun Poettering. Migrating Merchants: Trade, Nation, and Religion in Seventeenth-Century Hamburg and Portugal. Berlín, Boston, De Gruyter Oldenbourg, 2019, 389 pp. ISBN: 9783110469936. - Recio Morales, Óscar (Investigaciones de Historia Económica, 2020)
Sin resumen